Light perpetual - Sapkowski, Andrzej (Sapkowski, Andrzej. Trylogia husycka., 2022)
After his adventures in The Tower of Fools and Warriors of God, Reynevan is on the run again, harried by enemies--some human, and some mystical--at every turn. These are cruel and dangerous times for a man such as Reynevan, and to survive, he must set aside his history as a peaceful healer and idealist and play the brutal role of Hussite spy as crusades sweep through Silesia and the Czech Republic, and the world around him is forever changed.